(untitled) (Eurasian Medical Research Periodical, 2022)
Structural and organizational rearrangements occurring rapidly in the structure of the rat stomach in early postnatal ontogenesis, which enable us to take into account all the nuances when performing surgical surgery and reconstructive measures of the abdominal cavity organs in this case of the rat stomach. The last mentioned circumstance acquires great topicality, in particular, when carrying out preventive measures, such as prevention of possible complications after trauma. These data give us grounds to think about the necessity of profound research of structural and functional mechanisms of changing anatomico-topographic peculiarities of the stomach development of laboratory animals in norm. Experimental models of research on animals are of great importance in clinical medicine. When transferring the obtained experimental data from animals to humans, there are difficulties associated with the difference in anatomy and function of the organs.